2018
DOI: 10.33383/2017-075
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Lighting Fixtures and Installations for Greenhouses

Abstract: The article describes standards for industrial greenhouses irradiators (GOST R57671–2017), methods for measuring PAR region irradiance in overhead and rack-type installations (preliminary standard 211–2017), methods for measuring illuminance (FR.1.37.2017.27376) and photosynthetic irradiance (FR.1.37.2017.27375), photosynthetic photon flux (FR.1.37.2017.27374) and other lighting characteristics, energy efficiency factor calculations for LED installations in greenhouses (FR.1.37.2017.27373), which have been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…. Choice of the devices was an extraor dinary problem, because it was connected with in troduction of GOST P 57671-2017 and PNST 211-2017 developed in the VNISI [3][4][5].…”
Section: Research Methods and Experimental Installationmentioning
confidence: 99%
“…. Choice of the devices was an extraor dinary problem, because it was connected with in troduction of GOST P 57671-2017 and PNST 211-2017 developed in the VNISI [3][4][5].…”
Section: Research Methods and Experimental Installationmentioning
confidence: 99%
“…To measure the PPFD in the PAR region, a Li-190R quantum sensor with a Li-250A data logger (Li-COR, United States) was used, and a portable spectrometer MK 350S (UPRtek, Taiwan) was used to measure PIR spectra. The work carried out earlier showed that the indicated measuring devices provide the necessary accuracy and reliability of measurements (BOOS, et al, 2018), .…”
Section: Figure 4 -General View Of Experimental Irradiation Facilitiementioning
confidence: 99%